2016
DOI: 10.1007/s11695-016-2224-y
|View full text |Cite
|
Sign up to set email alerts
|

Results of Laparoscopic Sleeve Gastrectomy in 541 Consecutive Patients with Low Baseline Body Mass Index (30–35 kg/m2)

Abstract: With appropriate surgical expertise, LSG in patients with BMI 30-35 kg/m achieved excellent outcomes with a zero fistula rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Noun R et al have published their results of 541 patients with mild obesity in Lebanon with excellent outcomes with a zero-fistula rate. Interestingly, all patients in their study had to self-fund the surgery [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noun R et al have published their results of 541 patients with mild obesity in Lebanon with excellent outcomes with a zero-fistula rate. Interestingly, all patients in their study had to self-fund the surgery [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there is increasing interested in using bariatric surgery to treat diabetic patients without obesity. Several clinical studies have clearly indicated that weight-loss follows RYGB and VSG in non-obese or mildly obese subjects (Cohen et al, 2012;Noun et al, 2016;Ferraz et al, 2019). It is also noteworthy that gastrectomy done in non-obese subjects with gastric cancer also results in sustained weight loss, loss of appetite and abdominal discomfort (Adachi et al, 1999;Laffitte et al, 2015).…”
Section: Indiscriminate Weight-loss In the Non-obesementioning
confidence: 99%
“…Data at 12 months showed improvements in BMI from 33.1 kg/m 2 to 24.5 kg/m 2 and %EWL of 107.9%. Noun et al 13 examined 541 Lebanese patients who underwent LSG with a BMI of 30–35 kg/m 2 . Average BMI improved from a preoperative value of 32.59 kg/m 2 to 24.7, 24.9, and 26.4 kg/m 2 at 1, 2, and 5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10 Due to the stringent eligibility criteria outlined above, metabolic surgery has been performed on patients with class I obesity primarily outside of the United States. Several large randomized and observational studies examining metabolic surgery in class I obesity have been performed in Chile, 5,11 Brazil, 12 Lebanon, 13 and India. 14 These studies revealed positive results with regard to weight loss and comorbidity resolution.…”
mentioning
confidence: 99%